The Origins of the Income Theory of Money - Josef Menšík (Review of Economic Perspectives, 2015)
The income theory of money was conceived in the 19th century, and in the first half of the 20th century it formed the backbone of all the main monetary approaches of the time. Yet, since it did so mostly implicitly rather than explicitly, and since the later developments moved economic theory in a different direction, the income theory of money is hardly remembered at present. While mainly accounting for the origins of the approach, I am also offering a brief comparison with the present mainstream economics and I shortly address the question of the possible future of the theory too. The income theory of money explains how nominal prices are formed by interaction of nominal expenditures streams with real streams of goods sold. While various ideas leading to this theory were expressed already by John Law, Richard Cantillon, and Jean-Baptiste Say, it is perhaps only Thomas Tooke whom we might want to call the originator of the theory. Within the Classical School of Political Economy, Tooke's ideas were further elaborated by John Stuart Mill. The theory reached a momentous formulation in the works of Knut Wicksell, in many respects a similar exposition was delivered also by Friedrich Wieser. The recognition of the theory was impaired by a change of the main-stream paradigm as well as by a surge in emphasis laid on the quantitative modelling in economics. Yet, there are certain fundamental questions of the monetary theory which the general equilibrium style models cannot cope with, while the income theory of money can, at least to a certain degree. This might give the theory some hope for the future.
Keywords: 330